Dampak Flu Burung terhadap Produksi dan Pendapatan Peternak Ayam Ras Pedaging - Fadila Marga Saty; Irmayani Noer (Jurnal Ilmiah ESAI, 2010)
This research is aimed at finding the following ;(1) Testing heteoskedasdicity, multicolinearity, normal distribution and autocorrelation at Cobb-Douglas production function (2) Identifying production factors which influence broilers production in the avian flu infected area, using Cobb-Douglas production function analysis (3) Finding out the natural environment effect of avian flu to productivity and income of broiler farmer. This research was conducted in Tanjungkarang Barat, Telukbetung Barat, Sukarame, and Tanjung Senang. The method used was survey method.Â  The number of the sample was 25 chicken farmers. Cobb-Douglas function analysis was applied to view avian influenza effect to the income by using total output, total cost and output price variables. The result shows that the influencing factors are area, poultry and food at < 0.05 real point. Meanwhile vaccine and labor have no effect to the broiler production at > 5% real point. The dummy variable also has no effect. The effect of avian influenza to the average income at the infected area is bigger than at the uninfected area.Â Key word:, income, production, avian influenza(AI)